Aluminum intercalation and transport in TiO2(B) from first principles. (August 2019) - Tang, Weiqiang; Xuan, Jin; Wang, Huizhi; Zhao, Shuangliang; Liu, Honglai
Highlights: Thermodynamics of aluminum intercalation in TiO2(B) is predicted. The specific capacity with volume change is 755.05 mA h g −1 . It doubles the theoretical value of lithium storage in TiO2 (B). TiO2 (B) can offer new opportunities for aluminum-ion batteries. Abstract: Aluminum-ion batteries have emerged as a potential alternative to lithium-ion batteries by offering advantages such as abundant aluminum resources, low costs and good safety. Exploring suitable electrode materials lies at the heart of the development of aluminum-ion batteries. Relying on first-principles density functional theory, this study predicts the thermodynamics of aluminum intercalation in TiO2 (B) as a promising aluminum storage material. Three sites are identified to be the preferential locations for aluminum within the TiO2 (B) structure, and the stable intercalation site is found to prefer 5-fold coordinated to oxygen atoms with a slightly off-center position. The supercell volume change associated with aluminum intercalation is < 10%, and the thermodynamically maximum achievable Al/Ti ratios are respectively 0.6562 and 0.75 without and with considering this volume change. The corresponding specific capacities without and with volume change are calculated to be 660.62 mA h g −1 and 755.05 mA h g −1, doubling the theoretical value of lithium storage in TiO2 (B). As expected, aluminum has a very poor mobility in bulk TiO2 (B) due to its exceptionally high surface charge density, which would be addressable through the use of nanosized and defective materials. Our calculations suggest that TiO2 (B) can offer new opportunities for developing electrode materials for aluminum-ion batteries.